1979
DOI: 10.1111/j.1365-2621.1979.tb08540.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐pressure Liquid Chromatography of Cranberry Anthocyan

Abstract: The four major anthocyanins of cranberries were separated and purified by conventional paper chromatography. The purified individual anthocyanins were eluted from the paper by methanol-acetic acidwater (90:5:5) and concentrated on a rotary evaporator (<30"(Z). The individual anthocyanins were chromatographed separately and in a mixture by a reversed-phase high-pressure liquid chromategraphic (HPLC) system. Complete separation of all four anthocyanins took less than 1 hr 40 min. A SO-ml sample of commercial Cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…The identification of cyanidin‐3‐galactoside, cyanidin‐3‐arabinoside, peonidin‐3‐galactoside and peonidin‐3‐arabinoside in the 60% acidified methanol fraction in our study is supported by others that have identified these four major anthocyanins present in cranberry (Camire and Clydesdale 1979; Duthie and others 2006; Ohnishi and others 2006; Wilson and others 2008). Our results also showed that drying cranberry fruit using both VMD and FD methods resulted in a greater retention of these 4 anthocyanins compared to AD.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The identification of cyanidin‐3‐galactoside, cyanidin‐3‐arabinoside, peonidin‐3‐galactoside and peonidin‐3‐arabinoside in the 60% acidified methanol fraction in our study is supported by others that have identified these four major anthocyanins present in cranberry (Camire and Clydesdale 1979; Duthie and others 2006; Ohnishi and others 2006; Wilson and others 2008). Our results also showed that drying cranberry fruit using both VMD and FD methods resulted in a greater retention of these 4 anthocyanins compared to AD.…”
Section: Discussionsupporting
confidence: 88%
“…The gradient condition started with 95% A, linearly decreased to 75% A at 5 min, then to 60% A at 25 min, 5% A at 45 min, and linearly increased to 95% A at 55 min. Cyanidin‐3‐O‐rutinoside, cyanidin‐3‐O‐glucoside, peonidin‐3‐O‐glucoside, and petunidin‐3‐O‐glucoside were used as external standards (Camire and Clydesdale 1979; Ohnishi and others 2006). A cyanidin‐3‐rutinoside standard curve was produced and used to convert sample mAU×s to mg cyanidin‐3‐rutinoside equivalents per gram dry solid.…”
mentioning
confidence: 99%
“…Previous research has confirmed the presence of the 3-galactoside and 3-arabinoside of cyanidin and peonidin as the four major anthocyanins in cranberries with the additional small amount of cyanidin 3-glucoside or peonidin 3-glucoside (Camire and Clydesdale, 1979;Hong and Wrolstad, 1990a). Figure 5 shows the anthocyanin spectra from cranberry juice, closely matching the exact isotopic masses of cyanidin 3-arabinoside Cabernet Sauvignon (Wulf and Nagel, 1978) Merlot (Nagel and Wulf, 1979) Pinot Noir (Gao et al, 1997) delphinidin (theoretical value, 419.10), cyanidin 3-galactoside (449.11), peonidin 3-arabinoside (433.11), and peonidin 3-galactoside (463.12).…”
Section: Resultsmentioning
confidence: 82%
“…Anthocyanins from many plants, including fruits, have been separated and analyzed by paper chromatography (Dekazos, 1970;Camire and Clydesdale, 1979;Francis, 1985;Mazza and Velioglu, 1992;Gao and Cahoon, 1995), thin-layer chromatography (Wrolstad and Struthers, 1971; Barritt and Torre, 1973;Pouget et al, 1990;Dussi et al, 1995), and high-performance liquid chromatography (HPLC) (Wulf and Nagel, 1978;Camire and Clydesdale, 1979;Goiffon et al, 1991;Mazza and Velioglu, 1992;Gao and Mazza, 1994;Gao et al, 1997). HPLC coupled with photodiode array detection has often been used to qualitatively and quantitatively analyze anthocyanins and their glycosylated or acylated groups utilizing relative retention times and UV-vis spectra (Williams et al, 1978;Hong and Wrolstad, 1990a,b;Goiffon et al, 1991;Dallas et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In a subsequent study, Williams et al (1978) separated the anthocyanin pigments from grapes into twenty discrete peaks. Camire and Clydesdale (1979) also used HPLC to separate the four major anthocyanins of cranberries, following preliminary purification by ion-exchange chromatography (Chiriboga and Francis 1970). HPLC, involving radial compression, has been applied for the quantitative separation of anthocyanins of a number of Mtis viniferu wines (McCloskey and Yengoyan 1981b).…”
Section: As Indicated Bymentioning
confidence: 99%